Experimental Results From the Cryogenic Cooling of a Rotor Using an Internal Pump - Caughley, AJ; Lumsden, G; Badcock, R; Gschwendtner, M; Jeong, S (IOP Publishing, 2026)
Abstract: Superconducting motors are a route to the high power-to-weight ratio required for the electrification of large aircraft. In a synchronous superconducting motor, a popular configuration is to have the rotor with DC field coils and the stator with AC coils. This configuration makes the rotor cooling easier, as DC superconducting coils have few losses. However, the heat from the rotor still needs to be transferred across a high-speed rotating interface. Our proposed cooling method uses a helium gas circuit, internal to the rotor, that is circulated by the rotor’s motion against that of a cold stationary heat exchanger. Keeping the cold heat exchanger stationary reduces sealing requirements as the internally pumped gas can be kept near ambient pressure whilst the cold heat exchanger could be cooled by either pressurised cryogenic fluid, a two-phase medium, or a cryocooler. The internal rotor pump concept was first validated with a CFD model, which was in turn confirmed by experimentation. This paper presents the results of the proof-of-concept experiments that validated the CFD model and will present further improvements to the concept, demonstrating a feasible cooling method and its application to a superconducting rotor.
Keywords: 40 Engineering; 4009 Electronics, Sensors and Digital Hardware; 51 Physical Sciences; 7 Affordable and Clean Energy